Research Productivity of Faculty Members in Selected Private Colleges in the Province of Albay: Basis for Enhancing Research Culture - Onrubia, Elizabeth (JPAIR Multidisciplinary Research, 2024)
The study aimed to assess the research productivity of the faculty members in five private colleges in the province of Albay. This study used a multi-method approach in determining the research productivity, factors affecting the research productivity of respondents, and significant agreement on the factors affecting the research productivity of respondents among the private colleges in the province of Albay. A survey questionnaire, document analysis, statistical analysis, and literature review were incorporated. The study found varying levels of research productivity across the institutions. Researchership, institutional support, motivation, leadership practices, and research orientation all notably impact research productivity. The top areas influencing research productivity are time management, research-related development opportunities, and alignment of research agenda with institutional strengths. There is a statistically significant agreement on the factors affecting the research productivity of the respondents. Specific areas for interventions could aim to strengthen leadership practices that provide professional development opportunities, effective time management, research funding, faculty research writing aptitude, and a clear research agenda. A Research Development Program was designed based on the findings of the study. The components of this program are mentorship pairs and collaboration, internal research funding, seminar series, research facilities and resources, and research excellence recognition.
Keywords: Institutional Research; Research productivity; Research culture; Publication; Researchership; Research development program; multi-method; policy development; Philippines